Transatrial balloon atrial septostomy to facilitate weaning off venoarterial ECMO after pulmonary endarterectomy - AK, KORAY; TİRE, YAKUP; KARARMAZ, ALPER; YILDIZELİ, BEDRETTİN (My University, 2022)
Atrial septostomy has been the last resort in the management of patients with the right ventricular failure related to pulmonary hypertension before lung transplantation. In this paper, we present a simple and safe technique (transatrial approach) for balloon atrial septostomy in a patient who required central venoarterial extracorporeal membrane oxygenation after pulmonary endarterectomy.
Keywords: Tıp; Sağlık Bilimleri; Biyomedikal Mühendisliği; Mühendislik ve Teknoloji; Medicine; Health Sciences; Biomedical Engineering; Engineering and Technology; MÜHENDİSLİK, BİYOMEDİKAL; Mühendislik; Mühendislik, Bilişim ve Teknoloji (ENG); TRANSPLANTASYON; Klinik Tıp; Klinik Tıp (MED); ENGINEERING, BIOMEDICAL; ENGINEERING; Engineering, Computing & Technology (ENG); TRANSPLANTATION; CLINICAL MEDICINE; Clinical Medicine (MED); Transplantasyon; Genel Mühendislik; Biyomedikal mühendisliği; Mühendislik (çeşitli); Biyomühendislik; Fizik Bilimleri; Transplantation; General Engineering; Engineering (miscellaneous); Bioengineering; Physical Sciences; Pulmonary hypertension; artificial kidney; apheresis & detoxification techniques; pulmonary endarterectomy; ECMO; atrial septostomy; cardiopulmonary bypass; EXTRACORPOREAL MEMBRANE-OXYGENATION; LEFT-HEART DECOMPRESSION